Cardiac Arrest during Transesophageal Echocardiogram (TEE) due to Acute Right Ventricular Failure. (24th December 2021) - Kersey, Cooper B.; Medhane, Fitsumberhan; Pattock, Andrew M.; Liu, Linda; Huang, Gary; Lele, Abhijit V.; Kwon, Younghoon
Abstract : The case of a patient who suffered cardiac arrest while undergoing transesophageal echocardiography (TEE) is presented here. A 75-year-old man with moderate right ventricular (RV) dysfunction and pulmonary hypertension became bradycardic and hypotensive after receiving propofol for procedural sedation. His profound hypotension ultimately led to a pulseless electrical activity (PEA) cardiac arrest. TEE images captured immediately prior to cardiac arrest show a severely dilated and hypokinetic RV, consistent with acute right ventricular failure. This case highlights the potentially fatal consequences of procedural sedation in patients with RV dysfunction and pulmonary hypertension.